Peran Dukungan Emosional Keluarga Inti terhadap Kualitas Hidup Lansia: Systematic Literature Review - Siti Nabila W. Hamzah; Suci Gusnawati; Sri Ramadhani; Syahrita Nurul Aulia; Dian Novita Siswanti; Eka Sufartianinsih Jafar (CV. ITTC INDONESIA, 2026)
The quality of life of the elderly is influenced by physical, psychological, and social conditions. The aging process can lead to problems such as depression, anxiety, and loneliness, especially when there is a lack of family support and adequate social interaction. This study aims to examine the role of family support in the quality of life of the elderly using the Systematic Literature Review (SLR) method. The results show that family support plays an important role in improving the well-being of the elderly in physical, psychological, and social aspects. Elderly individuals who receive good support tend to be more independent, active, and have a better quality of life. Therefore, family is the main factor in improving the quality of life of the elderly